Painting of Krishna in seating posture flanked by Gopis (female cowherd) - Temples of India Project Team (Jio Institute, 2024)
Paintings above the doorway in the exterior walls of the Bhandasar Temple. The horizontal block at the centre of the upper set also has a painting of Krishna in seating posture, flanked by gopis (female cowherd). Krishna is shown blue-skinned and holds two lotuses in the upper two hands.